The Assessment: Finance, Law, and Growth. - Mayer, C; Sussman, O (2001)
This article reviews the development of corporate finance from domestic analyses to international comparisons of financial systems, to comparative corporate governance, to law and finance, and most recently to politics and finance. It describes how both theoretical developments and empirical evidence have guided this research agenda. It considers the lessons that can be learnt from the newly emerging literatures and considers the policy implications that can be derived. It argues that while strong policy prescriptions are frequently proposed, there are many unresolved theoretical and empirical issues which suggest that caution should be exercised in drawing policy conclusions.